Report on proposed new interior design of Chevrolet 3S Centre for Hicom-Chevrolet Sdn. Bhd. No 18, Jalan Pelukis U1/46, Seksyen U1, Bandar Shah Alam, Selangor Darul Ehsan / Aminul Haq Zainul Rashid - Zainul Rashid, Aminul Haq (Faculty of Architecture, Planning and Surveying, 2010)
The student’s final project of Diploma in Interior Design reveals students knowledge on all aspects in interior design from basic principle of designs to the final presentation of the proposed project. This includes understanding on the criteria of the chosen site for the proposed project, as well as knowledge on identifying structures of the existing building, along with its mechanical and electrical systems, plumbing systems and existing materials. The chosen project for the final project is to Proposed New Interior Design of Chevrolet 3S Centre for Hicom-Chevrolet Sdn. Bhd. at No. 18, Jalan Pelukis U1/46, Seksyen U1, Bandar Shah Alam, Selangor Darul Ehsan. The client, Hicom-Chevrolet Sdn. Bhd. is expected to increase more specialty 3S Centre throughout Malaysia, including Sabah and Sarawak. The chosen concept and image not only fulfilled client’s requirement, but also must reflect client’s character and corporate image as well as to give a positive impact to the performance of workers inside the centre so that it will inculcate workers to work even harder. Before achieving a desired design that is going to be implemented inside the centre, some analytical works need to be carried out such as collecting datas from client regarding to their nature of business. Certain information are gained through the interview with the client itself, observation and internet.